Kemitraan antara Petani Kopi dengan Perusahaan (Studi Kasus Kintamani) - Ginanjar Dwi Cahyanto; Agung Wibowo; Putri Permatasari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The partnership between the Kintamani people's coffee farmers and the company is expected to absorb overall production as well as increase the coffee production of the farmers and be mutually beneficial. PT. Perkebunan Nusantara XII is a company that is a partner of the Kintamani people's coffee farmers, precisely in the Blawan Bondowoso Plantation by forming a core plasma partnership pattern. This study aims to describe the partnership conditions that exist between the Kintamani people's coffee farmers and the company. The qualitative data analysis technique is done by collecting data until it is saturated and then conveyed interactively. Research showed that there were three parties involved between the company, smallholder coffee farmers and BNI. The company as the core company provides assistance, procurement and purchasing facilities to smallholder coffee farmers as a plasma. In addition, the smallholder coffee farmers as plasma have an obligation to provide their coffee production to the nucleus company. The purchase of coffee production by the core company involves BNI as the party that distributes capital loans in the form of People's Business Credit (KUR) to plasma. The impact of partnerships with companies is felt by smallholder coffee farmers, such as the smooth marketing of coffee. The hope of partnership farmers can be continuous and implemented in the long term.Keywords: Coffee, Corporate, Nucleus-plasma Pattern, Partnership, Smallholder Coffee FarmersAbstrakKemitraan antara petani kopi rakyat Kintamani dengan perusahaan diharapkan dapat menyerap produksi secara keseluruhan sekaligus peningkatan produksi kopi petani dan bisa saling menguntungkan. PT. Perkebunan Nusantara XII merupakan perusahaan yang menjadi mitra petani kopi rakyat Kintamani tepatnya di Kebun Blawan Bondowoso dengan membentuk suatu pola kemitraan inti plasma. Penelitian ini bertujuan mendeskripsikan kondisi kemitraan yang terjalin antara petani kopi rakyat Kintamani dengan perusahaan. Teknik analisis data kualitatif dilakukan dengan mengumpulkan data hingga jenuh kemudian disampaikan secara interaktif. Penelitian menunjukkan terbentuk tiga pihak yang berhubungan antara perusahaan, petani kopi rakyat dan BNI. Perusahaan sebagai perusahaan inti memberikan fasilitas pendampingan, pengadaan dan pembelian kepada petani kopi rakyat sebagai plasmanya. Di samping itu petani kopi rakyat sebagai plasma memiliki kewajiban memberikan hasil produksi kopinya kepada perusahaan inti. Pembelian hasil produksi kopi oleh perusahaan inti melibatkan BNI sebagai pihak yang menyalurkan pinjaman modal berupa Kredit Usaha Rakyat (KUR) kepada plasma. Dampak kemitraan dengan perusahaan yang dirasakan petani kopi rakyat seperti lancarnya pemasaran kopi. Harapan petani kemitraan bisa kontinu dan dilaksanakan dalam jangka panjang.Kata kunci: Kopi, Kemitraan, Perusahaan, Petani Kopi Rakyat, Pola Inti-Plasma